2016
DOI: 10.3389/fncel.2016.00275
|View full text |Cite
|
Sign up to set email alerts
|

Positive Allosteric Modulation of Insect Olfactory Receptor Function by ORco Agonists

Abstract: Insect olfactory receptors (ORs) are heteromeric ligand-gated cation channels composed of a common olfactory receptor subunit (ORco) and a variable subunit (ORx) of as yet unknown structures and undetermined stoichiometries. In this study, we examined the allosteric modulation exerted on Anopheles gambiae heteromeric ORx/ORco olfactory receptors in vitro by a specific class of ORco agonists (OAs) comprising ORcoRAM2 and VUAA1. High OA concentrations produced stronger functional responses in cells expressing he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
(106 reference statements)
0
19
0
Order By: Relevance
“…Similarly to the working scheme presented earlier (34,35), the general principle for agonist/antagonist screening has been that the addition of the ethanol solvent or a compound devoid of ORco-binding activity would allow the appearance of cellular luminescence upon sequential addition of the ORco agonist, while the addition of a compound acting as an ORco antagonist would prevent, partially or completely, the appearance of luminescence in the cells upon secondary addition of the ORco agonist. The same expression platform also allows the identification of compounds acting as ORco agonists.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to the working scheme presented earlier (34,35), the general principle for agonist/antagonist screening has been that the addition of the ethanol solvent or a compound devoid of ORco-binding activity would allow the appearance of cellular luminescence upon sequential addition of the ORco agonist, while the addition of a compound acting as an ORco antagonist would prevent, partially or completely, the appearance of luminescence in the cells upon secondary addition of the ORco agonist. The same expression platform also allows the identification of compounds acting as ORco agonists.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we have shown that An. gambiae ORx/Orco functional responses elicited by ORxspecific odor agonists were enhanced both in terms of potency and efficacy by one to two orders of magnitude in the presence of an OA (35). These findings also pointed to the induction of conformational rearrangements in ORx ligandbound ORx/ORco receptor complexes caused by the binding of the OA and resulting in enhanced inward currents into the receptor-expressing cells.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In subsequent studies that revealed extraordinarily narrow structure-activity relationships, several additional VUAA-class actives were identified and characterized that now comprise several more potent agonists (including VUAA4 used here), a non-competitive antagonist (VUANT1, used here) as well as an inactive structural analog (VUAA0, used here) (28, 46-49). Further studies, including single-sensillum recordings of female-specific basiconic sensilla in C. floridanus , have demonstrated that the potency of these modulators in both volatile and non-volatile form is conserved across a wide range of insect orders (40, 47, 50-52). Indeed, VUAA-Orco interactions have recently been directly confirmed by cryo-electron microscopy studies characterizing the structure of an Orco tetramer from the parasitic fig wasp Apocrypta bakeri (53).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of putative insect ORs identified has escalated with the increasing number of fully sequenced genomes (Fox et al, 2002;Krieger et al, 2002;Holt et al, 2003;Krieger et al, 2004;Sakurai et al, 2004;Robertson & Wanner, 2006;The International Aphid Genomics Consortium, 2010;Cao et al, 2014) and with the employment of antennal transcriptome analysis (Grosse-Wilde et al, 2011;Liu et al, 2012;Nishimura et al, 2012;Zhang et al, 2014). Additionally, many ORs in several species have been studied by heterologous expression in the Xenopus oocyte system (Nakagawa et al, 2005;Wanner et al, 2010;Wang et al, 2011;Liu et al, 2013;Zhang et al, 2013), in HEK293 cells (Grosse-Wilde et al, 2006;Grosse-Wilde et al, 2007;Forstner et al, 2009), in Bm5 (Tsitoura et al, 2010), in HighFive cells (Tsitoura et al, 2010;Tsitoura et al, 2015;Tsitoura & Iatrou, 2016) and in Drosophila OSNs (Dobritsa et al, 2003;Hallem et al, 2004b;Montagne et al, 2012). The decoding of the olfaction mechanism in insects is helpful for screening and developing effective insect-behavior regulators for pest control.…”
Section: Introductionmentioning
confidence: 99%